Multiwave matrix polarization lidar - Volkov, Sergey N. физик; Bryukhanov, Ilia D.; Samokhvalov, Ignatii V. 1943-; Kim, Dukhyeon; Noh, Youngmin (Atmosphere)
Remote control of the state of the atmosphere is an urgent problem nowadays. The problem of remote monitoring of the optical parameters of the atmosphere is solved using a matrix polarization lidar (MPL). The scattering matrix obtained from polarization measurements contains complete information on the scattering parameters in the atmosphere. The purpose of the present research is the derivation of the theory and description of methods for solving problems of practical implementation of the multiwave MPL (MMPL). The problem is considered within the framework of the concept of the uniﬁed methodological approach to polarization studies. The MMPL operation principle is based on simultaneous use for sensing of the ﬁrst, second, and third harmonics of radiation of a widespread Nd:YAG laser. The basis for achieving this purpose is provided by new methods of optical selection of the polarization components of radiation received in the experiment, methods of conducting polarization studies, and new solutions in experimental data processing methods. It has been shown that this challenge can be solved within the framework of simple solutions. Thus, the proposed MMPL is structurally simple and compact and can be implemented in mobile polarization lidar systems.